Influence of the Macroclimatic Oscillations in the Gachaneca River Basin Weather Patterns; Boyaca-Colombia - Luís Beltrán (10393075); Diana Cristina Díaz (10393078) (2020)
Abstract To study the influence of macroclimatic oscillations in the Gachaneca river basin this work studies the variability of minimum and maximum temperature and standardized precipitation indices in the basin area between the years 1982 and 2015, and evaluated the relation among these variables with El Niño Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Quasi-Biennial Oscillation (OCB) by canonical correlation analysis. The results reveal that percentages of variance explained by macroclimatic phenomena in December-February range between 34% and 38%, in March-May between 15% and 20%, in June-August between 15% and 25% and in September- November between 21% and 34%. The most influential phenomenon is ENSO, followed by NAO. During DEF the study area is more exposed to dry events that increase the risk of depletion of water resources due to the warm phase of ENSO. The NAO can indirectly reinforce or mitigate drought events due to its relationship with the magnitude of the trade winds and the variability of the tropical Atlantic that have an impact on the position of the ITCZ and the convective processes of the region.